PEMANFAATAN LAHAN SEMPIT MENUJU KEJUARAAN LOMBA PROGRAM KAMPUNG LINGKUNGAN ( PROKLIM ) DI KECAMATAN JAMBANGAN SURABAYA - Markus Patiung; Erna Haryanti; Dwie Retna.S; Risnani Pudji R; Adi W (Indonesian Collaboration Journal of Community Services, 2021)
This Community service aims to motivate people who have lost their jobs due to the impact of the COVID-19 pandemic. Through this activity the community will have productive skills that can support household income. In detail, the objectives of this  Penmas are: a) Helping solve problems in overcoming the impact of the Covid 19 pandemic. b) Transferring knowledge and technology through counseling and mentoring activities on business opportunities to utilize narrow land through vegetable cultivation. c) Growing new entrepreneurs who are as a driver of the community's economy in the Jambangan Village, Surabaya City. this Penmas applies the full participation method, which is to provide opportunities for the target together with the implementing team to synergize in planning, organizing, implementing and evaluating this Community Service activity. The knowledge and technology transferred in this activity includes the growth of an entrepreneurial spirit, practical marketing strategies, institutional management as well as training and mentoring for cultivation on narrow land. The high enthusiasm not only makes the community able to apply profitable cultivation techniques, but this community service activity also motivates the community to create a clean and productive environment and even participate in the environmental village program competition championship (PROKLIM)